Reading Swift's poetry - Cook, Daniel 1981- (Cambridge University Press, 2020)
"Part way through his most famous self-elegy, Jonathan Swift coined one of the greatest one-line gags in poetry: 'what he writ was all his own'. The ostensibly proprietorial phrase was brazenly lifted from John Denham's On Mr Abraham Cowley: To him no Author was unknown, Yet what he wrote was all his own. Denham praises Cowley for writing original verse under the appropriate influence of prominent models old and new. In Swift's poem, more than half a century later, the venerable art of imitation (imitatio veterum) had been displaced by the dubious threat of theft (stealing hints). What does it mean to steal a hint? 'To steal another's idea is wrong', as James McLaverty says; but 'to take it and adapt it (as Swift does with the La Rochefoucauld maxim that stimulates the Verses or with Denham's couplet in these lines) is a vital aspect of invention'. A hint can be gifted and regifted among likeminded writers. Swift gave John Gay the idea for The Beggar's Opera, though the latter preferred 'to have my own Scheme and to treat it in my own way'"
Includes bibliographical references and index
Keywords: Swift, Jonathan -- 1667-1745; Lyrik; Swift, Jonathan / 1667-1745 / Poetic works; Swift, Jonathan / 1667-1745 / Criticism and interpretation